2021
DOI: 10.1186/s13018-021-02858-9
|View full text |Cite
|
Sign up to set email alerts
|

The association the patient-reported outcomes after periacetabular osteotomy with radiographic features: a short-term retrospective study

Abstract: Background Bernese periacetabular osteotomy (PAO) is an effective treatment for patients with developmental dysplasia of the hip (DDH). PAO has been widely used in China, but few follow-up outcomes have been reported in the international community. Moreover, the risk factors affecting patient-reported outcomes have not been discussed in recent studies. In this study, patient-reported outcomes after PAO were reported, and risk factors affecting patient-reported outcomes were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Whereas Holleyman et al reported a preoperative value of 30.0 for the iHOT-12, the patient population of Fan et al had a preoperative iHOT-12 value of 60.9, whereas our patient cohort presented 40.0. The literature reports an increase in iHOT-12 around 30 points for PAO in patients with DDH, as we found an increase of 31.0 points 32 , 33 . As an increase of 13 points was assessed as the minimal clinical important difference in iHOT-12 score by Nwachukwu et al both the control group as well as the LSTV group exceeded the threshold for minimal clinical difference 34 .…”
Section: Discussionsupporting
confidence: 67%
“…Whereas Holleyman et al reported a preoperative value of 30.0 for the iHOT-12, the patient population of Fan et al had a preoperative iHOT-12 value of 60.9, whereas our patient cohort presented 40.0. The literature reports an increase in iHOT-12 around 30 points for PAO in patients with DDH, as we found an increase of 31.0 points 32 , 33 . As an increase of 13 points was assessed as the minimal clinical important difference in iHOT-12 score by Nwachukwu et al both the control group as well as the LSTV group exceeded the threshold for minimal clinical difference 34 .…”
Section: Discussionsupporting
confidence: 67%
“…We included articles in which the PAO was performed in patients with no prior intervention for symptomatic hip dysplasia and in which both preoperative and postoperative patient-reported outcomes were reported. Articles that reported either the HHS, modified Harris Hip Score (mHHS), or WOMAC were included [8][9][10][11][12][13][14].…”
Section: Review Methodsmentioning
confidence: 99%
“…Patients with an oversized postoperative LCEA and poor or fair preoperative hip joint congruency were correlated with poor postoperative patient-reported outcomes via the HHS. A Tönnis angle of −10° to 0° was however determined to be a factor correlated with success, as evidenced by a satisfactory postoperative HHS [ 8 ].…”
Section: Reviewmentioning
confidence: 99%
“…Axial and anteroposterior plain radiographs of the pelvis were obtained preoperatively to identify the cam deformity and assess the Tönnis grade, the lateral centred edge angle (LCEA), and the alpha angle [30,31]. At admission, the following data were recorded: age, gender, duration of symptoms before surgery, side, and BMI (Kg/ m 2 ).…”
Section: Outcomes Of Interestmentioning
confidence: 99%